Application of the POAC Model in Islamic-Based Education Administration in the Package C Equality Program at PKBM Leadership Cendikia Gowa - Jumriani, Jumriani; Lisaw, Irwani; Jumadi, Jumadi (Widyagogik, 2025)
This study aims to analyze the application of the POAC model (Planning, Organizing, Actuating, Controlling) in Islamic-based educational administration within the Paket C Equivalency Program at PKBM Leadership Cendikia Gowa. This research employed a qualitative approach with a case study design. The participants consisted of administrators, tutors, learners, and parents, selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña. The findings reveal that: (1) Planning was carried out through participatory deliberation to design learning programs based on the needs of the learners; (2) Organizing was implemented by assigning teaching responsibilities according to tutors’ competencies, guided by the Islamic value of justice (‘adl); (3) The implementation of learning integrated academic achievement with character development through Qur’anic recitation, collective prayer, and exemplary conduct demonstrated by tutors; and (4) Evaluation was conducted through attendance monitoring, learning assessment, and end-of-semester reflective discussions. The integration of Islamic values such as trustworthiness (amanah), consultation (syura), and moral exemplarity strengthens the effectiveness of educational administration and contributes to the character formation of learners.